Technical Efficiency of Rice Farming Around the Nickel Mining in Konawe Selatan District - Hasriati, Hasriati; Ari, Rustan; Harianti, Harianti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
South Konawe Regency has vast potential agricultural land, It can support the regional economy by supplying the food needs of the community and being a major player in trade across districts. In addition to providing food, the agricultural sector also serves as a market for goods produced by the industrial sector in rural communities and urban areas, a source of labor for industry, a source of capital for modern economic growth, particularly in its early stages, and a source of foreign exchange. Policy support is needed from the government in developing the agricultural sector considering the importance of synergy between the agricultural and mining sectors to minimize negative impacts in order to achieve economic balance so that it becomes the basis for local governments in taking appropriate policies to support the agricultural sector amidst mining activities. The purpose of this study is to examine lowland rice farming's technical effectiveness and production characteristics in the vicinity of South Konawe Regency's nickel mine. The data collected used primary and secondary data, with a total of 20 farmers as respondents. Stochastic Frontier Analysis (SFA) was utilized to analyze the data. The findings of the study indicate that lowland rice farming is technically efficient when it is conducted near nickel mining and that the production elements that actually affect lowland rice farming include land area, labour force, urea and NPK fertilisers, and insecticides.